Dabo - Angeles, Sonny; Capul, Belina SB; Flores, John Marin (Philippine Information Agency [producer], 1989)
A documentary-drama on the pains and pleasures of growing up. Focus of the film is on problems in family relationship, particularly with parents, teachers and kins which sometimes lead to drug addiction and other social ills and vices.